PROSES PENYELESAIAN TINDAK PIDANA SECARA DAMAI DI POLRESTA SIDOARJO - Muhamad, Fajar muhamad; Astuti, Pudji (Universitas Negeri Surabaya)
Abstract The peaceful settlement of criminal acts through penal mediation is not known in the Criminal Procedure Law and the Indonesian National Police Law nor does it regulate the mediation of penalties in the police, so all criminal acts must be resolved by the provisions based on the Criminal Procedure Law. However, with the applicable provisions, mediation can be carried out if it is not detrimental to one of the parties so that there is a category as a benchmark for criminal cases that can be resolved by penal mediation, namely including the category of complaint offense and including non-criminal offenses. In practice, police officers still resolve criminal cases by Alternative Dispute Resolution regardless of the category of criminal cases that can be peaceful. The purpose of this study was to determine the reasons for police officers who resolved criminal acts by alternative Dispute Resolution at the Sidoarjo Resorts Police and which cases could be resolved by penal mediation. This research is a qualitative descriptive study with informants from members of the Sidoarjo Resorts Police. Data obtained by interview and documentation. The collected data were analyzed qualitatively. The results showed that police officers who resolve criminal acts amicably aim to resolve cases briefly but are not following the applicable procedural law in the absence of a prior investigation process. The case that can be resolved at the Sidoarjo Resorts Police namely: assault, theft, fraud, embezzlement, sexual harassment, domestic violence, traffic accidents. Keywords: Alternative Dispute Resolution, Penal Mediation, Crime, Police